2017
DOI: 10.1079/pavsnnr201712045
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen gas and its role in cell signalling.

Abstract: Hydrogen gas (H2) was once thought to be inert in biological systems but it has now become apparent that exposure of a wide range of organisms, including animals and plants, to H2 or hydrogen-rich water has beneficial effects. It is involved in plant development, and alleviation of stress and illness, such as reperfusion injury. Here, an overview of how H2 interacts with organisms is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Lastly, it has recently been suggested that signaling in animals and plants may involve hydrogen gas (H 2 ) [ 76 ]. The presence of H 2 may alter antioxidant levels in cells [ 77 ] and so indirectly alter NO metabolism.…”
Section: Interactions Of Nitric Oxide With Other Reactive Signalsmentioning
confidence: 99%
“…Lastly, it has recently been suggested that signaling in animals and plants may involve hydrogen gas (H 2 ) [ 76 ]. The presence of H 2 may alter antioxidant levels in cells [ 77 ] and so indirectly alter NO metabolism.…”
Section: Interactions Of Nitric Oxide With Other Reactive Signalsmentioning
confidence: 99%
“…Molecular hydrogen (H 2 ) is now recognized to have biochemical effects in both animals [ 1 , 2 ] and plants [ 3 , 4 ]. Although it is a relatively inert gas, H 2 appears to have profound effects on cell activity, which can be harnessed to help plant growth, survival, and productivity [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several other reactive compounds also need to be considered to be involved in the control of cellular function [1]. Among these is hydrogen gas (H2) [3], a compound gaining prominence in the literature. However, to be considered as part of a suite of signaling molecules, the production, movement, perception, roles, and removal of the signaling compound need to be considered [2], and this would also apply to H2 if it is to be accepted as a regulatory component in cells.…”
Section: Introductionmentioning
confidence: 99%
“…In treating organisms with H2, there are various methods which can be used [3]. Although H2 can be used in the gaseous form, more often a saturated solution is created and added to the biological system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation